Rancang Bangun Sistem Informasi Manajemen Pengabdian Masyarakat Berbasis Web di Politeknik Elektronika Negeri Surabaya - Kholid Fathoni; Ira Prasetyaningrum; Franciscus Anggara Pradana Herdi Praja (STMIK Budi Darma, 2019)
Community service activities as mentioned in Undang-Undang of Indonesia State No. 20 of 2003 concerning the National Education system, article 20 is one of the mandates of the Tri Dharma of Higher Education, including the Politeknik Elektronika Negeri Surabaya (PENS). Management of community service in the Research and Community Service Center (P3M) is still manual in collecting, storing and processing service data. The system raises several problems including delays, inaccuracies and excessive workload for administrators and operators and stakeholders in processing and accessing data of community service. Therefore it is necessary to make an application for a multiplatform-based information system to handle transactions and management of various community service data. This application handles the collection of proposal data, progress reports and final reports and handles proposal selection transactions, monitoring and evaluating progress reports, as well as seminar results, including the plotting of service reviewers. This system uses PHP framework and MySQL database management system. The test results show that all application functions are running well and make it easy for all service stakeholders to manage community service activities.